Mothers' knowledge of premature newborn care and application of Kangaroo Mother Care at home - Marcilene Pimentel Gomes; Salma Brito Saráty; Alexandre Aguiar Pereira; Andressa Tavares Parente; Mary Elizabeth de Santana; Maria de Nazaré da Silva Cruz; Andreza Duarte Martins Figueira (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to identify mothers' knowledge about premature newborn care and application of Kangaroo Mother Care at home. Methods: a descriptive, qualitative study carried out with 15 mothers of premature newborns in a reference Maternal and Child Hospital in northern Brazil using two semi-structured interviews with open- and closed-ended questions. The testimonies were analyzed using thematic analysis technique, proposed by Bardin. Results: two thematic categories originated: "Caring for a premature newborn at home: strengths and weaknesses" and "Applying Kangaroo Mother Care at home: new knowledge acquired during hospitalization". Final considerations: the speeches of the interviewed mothers pointed out their knowledge about home care of premature NBs and understanding the importance of Kangaroo Mother Care, mainly acquired and improved with the guidance of professionals during hospitalization and application of the method, in addition to fears, possible difficulties in home care and the need to be better informed at hospital discharge.